Using composition trees to matching software requirements—An external agency's approach to support software acquisition. (24th January 2022) - Zhang, Shaoyang; Wen, Lian; Anwer, Sajid; Liu, Baoxing
Abstract: To improve their competitiveness, companies should acquire the latest software systems. However, many small or medium‐sized companies might not be able to afford a proper software acquisition process without the resource and technical support essential for acquiring the right software system. This article proposes a meta‐process, software acquisition with an external agent (SAEA), that includes a new industry role, external agent, to substitute for that support. SAEA will significantly reduce the cost of the software acquisition process. For implementing SAEA, the authors also introduce composition trees as a modelling language to collect, integrate, and compare all software requirements from different stakeholders and to identify issues during the software acquisition process. Finally, a real industry case study, for which this process has been successfully implemented, has been provided to illustrate our approach.